Recent Advances in the Synthesis of K-Vitamins - August Rüttimann (CHIMIA)
The term «Vitamin K» is a collective name and embraces a whole series of 2-methyl-1,4- naphthoquinone derivatives which play a decisive part in the control of blood clotting. The most important representative, vitamin K1 (phylloquinone), has a phytyl group as substituent in the 3-position. On the other hand, K2-vitamins (menaquinones) possess polyunsaturated, isoprenoid side-chains of varying length in this position. – The first technical syntheses of vitamin K. were accomplished by Isler (F. Hoffmann-La Roche & Co. Ltd.) and Hirschmann (Merck & Co. INC., Research Laboratories) more than thirty years ago. In analogy to Fieser’s early work, a protected menadiol is reacted with isophytol or phytol in a Friedel-Crafts type alkylation and vitamin K1 is obtained as a mixture of E- and Z-isomers. – However, biological investigations on vitamin K deficient chicks have clearly indicated that the Z-isomer has virtually no vitamin K activity. In addition, the large number of reaction steps make these syntheses rather unattractive in terms of economy. Therefore, the design of a highly stereoselective and economical synthesis of (E)-vitamin K, has received increasing attention during the last decade; in particular, methodology had to be developed for an efficient coupling of the (E)-phytyl side-chain with the naphthoquinone ring with full retention of the trans double bond.